Estudo do valor nutritivo do farelo de guandu [Cajanus cajan (L.) Miilps] var. fava larga na alimentação de frangos de corte. 1. Avaliação do tratamento térmico - Pezzato, Antonio Celso [UNESP]; Silveira, Antonio Carlos [UNESP]; Furlan, L. R.; Pezzato, Luiz Edivaldo [UNESP]; Costa, Ciniro [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1995)
The experiment was conducted to evaluate pigeon pea (Cajanus cajan) protein in broiler chicks (up to 28 days of age) feeding, as compared to soybean (Glycine mar) protein, In the experiment the effects of temperature and autoclaving on antinutritional factors on pigeon pea meal were studied. Temperatures of 100, 110 e 120 degrees C and times of autoclaving of 10, 20 and 30 minutes were applied using a two-way factorial design, replicated in four times. Underheating and overheating during the process of inactivation of proteases inhibiting were evaluated by ureatic activity and protein solubility analysis, after the grains were dried and ground. After 28 days, the best time of autoclaving was 20 minutes (p<,05) irrespectively of temperature, which lead to a lower feed consuption. There were no histopathological alterations in kidney, liver, pancreas, heart and intestines of the broilers.

O experimento teve como objetivo avaliar o efeito do tratamento térmico sobre os fatores antinutricionais presentes no guandu. Foram utilizados 288 pintos de corte em duas baterias metálicas, distribuídos num delineamento experimental em quatro blocos, num esquema fatorial de 3 x 3, em três temperaturas: 100, 110 a 120 °C e três tempos de autoclavagem: 10, 20 e 30 minutos. Após o processamento, secagem e moagem dos grãos, foram analisadas a atividade ureática e a solubilidade da proteína como parâmetros de sub ou superaquecimento durante o processo de inativação dos inibidores de proteases. No final, constatou-se que o melhor tratamento foi proporcionado pelo guandu tratado durante 20 minutos (p < ,05) independentemente das temperaturas de autoclavagem, resultando num menor consumo de ração. As aves não apresentaram nenhuma alteração histopatológica nos rins, no fígado, no pâncreas, no coração e nos intestinos.
Study on the nutrition value of pigeon pea meal [Cajanus-cajan (l) millps] in broiler feed .1. evaluation of thermal-treatment
Keywords: PROTEASE INHIBITORS; UREATIC ACTIVITY; PROTEIN SOLUBILITY; EFFICIENCY OF PROTEIN UTILIZATION; EFFICIENCY OF METABOLIZABLE ENERGY UTILIZATION